Negative Religious Coping Predicts Disordered Eating Pathology Among Orthodox Jewish Adolescent Girls - Latzer, Yael (Journal of religion and health, 2015)
Recent research suggests the importance of exploring religious and spiritual factors in relation to the continuum of disordered eating. This continuum ranges from mild disordered eating behaviors and attitudes to moderate levels of disordered eating pathology (DEP) through full-blown clinical levels of eating disorders (EDs). The current study is the first to explore the role that religious coping (both positive and negative) plays in the development DEP, which is considered a risk factor for the development of EDs. In addition, the study aims to describe levels of DEP among a non-clinical sample of 102 Orthodox Jewish adolescent females. Participants completed a questionnaire measuring religious coping strategies, DEP and self-esteem. Results indicated that greater use of negative religious coping was associated with higher levels of DEP. Mediation analyses suggested that greater negative religious coping is related to lower levels of self-esteem, which accounts for higher levels of DEP. Furthermore, findings revealed relatively lower overall levels of DEP among this sample, compared to similar populations in Israel and the USA. These results suggest that a strong religious and spiritual identity may serve as a protective factor against DEP.